Comparative evaluation of two prophylactic intravenous bolus doses of phenylephrine for prevention of spinal-induced hypotension in elective cesarean sections: a prospective and randomized study - Paccha, Sushma; Srisha, Amith; T. R., Raghavendra (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Hypotension is a common and clinically significant complication associated with spinal anesthesia during cesarean section, often persisting despite standard preventive strategies such as fluid preloading and left uterine displacement. Vasopressors like phenylephrine are routinely employed to counteract the hemodynamic instability, yet limited data exist comparing different fixed bolus doses of phenylephrine for prophylaxis against spinal-induced hypotension in obstetric anesthesia. This study aimed to evaluate and compare the efficacy and safety of two intravenous bolus doses of phenylephrine-150 micrograms and 200 micrograms-administered immediately following spinal anesthesia, in preventing maternal hypotension during cesarean delivery. Methods: A prospective, randomized, double-blind study was conducted at Adichunchanagiri Institute of Medical Sciences, Karnataka, India involving 60 parturients scheduled for elective cesarean section. Group A received 150 µg and group B received 200 µg phenylephrine IV bolus immediately after spinal anesthesia. Hemodynamic parameters, incidence of hypotension and bradycardia, requirement of rescue boluses, and Apgar scores were recorded. Results: The incidence of hypotension was 16.6% in both groups. Group B showed a significantly higher incidence of bradycardia (43.3%) compared to group A (20%, p<0.05). Group A demonstrated better hemodynamic stability with fewer rescue interventions. Neonatal outcomes were similar in both groups. Conclusions: A 150 µg bolus of phenylephrine is as effective as 200 µg in preventing hypotension following spinal anesthesia in cesarean delivery, with fewer adverse effects. It is recommended as the preferred dose for prophylaxis.